Low-current operations in 4F2-compatible Ta2O5-based complementary resistive switches. (25th September 2015) - Breuer, Thomas; Siemon, Anne; Linn, Eike; Menzel, Stephan; Waser, Rainer; Rana, Vikas
Abstract: Complementary resistive switches (CRS), which consist of two anti-serially connected bipolar switching ReRAM cells, can reduce sneak path currents in passive crossbar arrays. However, the high operation current restrains the implementation of the CRS device. In this article, we present low current operation (<300 μ A) of vertically stacked, 4 F 2 -compatible Ta2 O5 -based CRS devices exhibiting two terminals. Two types of devices, either offering a nano- or a micrometer scale bottom cell (BC), are considered. The top cell (TC) in both configurations is designed of micrometer size. A novel three-step electroforming procedure for the vertical CRS device having no access to the middle electrode is exemplified and compared to the conventional forming procedure using three-terminal CRS devices. This three-step electroforming procedure provides adjustment of the maximum switching current in the nano-BC CRS: a low-level current compliance during forming enables low current CRS operation in subsequent switching cycles. Further, the nano-BC CRS shows the stable switching up to 10 4 cycles whereas the micro-BC CRS endures up to 10 6 cycles.